The Efficacy of Passive Ultrasonic Activation of Organic Solvents on Dissolving Two Root Canal Sealers - Trevisan, LetÃcia; Huerta, Isadora Razzera; Michelon, Carina; Bello, Mariana De Carlo; Pillar, Rafael; Bier, Carlos Alexandre Souza (Iranian Endodontic Journal, 2017)
Introduction: The aim of this in vitro study was to evaluate the dissolving efficacy of eucalyptol and orange oil solvents associated with passive ultrasonic activation (PUA) in zinc oxide-eugenol (ZOE) based and epoxy resin-based root canal sealers. Methods and Materials: Seventy samples of each sealer were prepared and then randomized according to the solvent and the time of the ultrasonic activation (n=5). The mean amount of weight loss of sealers was calculated in percentages and was analyzed by using the Kruskal-Wallis and Bonferroni post-hoc tests. Results: The greatest values of weight loss were obtained with the ZOE sealer groups (P<0.05), regardless of the solvent that was used. An application of PUA for 3 min, with a renewal of orange oil solvent each min, showed the greatest percentage of weight loss in ZOE sealer compared to the others templates (P<0.05). Neither the solvent nor the different times had any influence on the weight loss of the resin sealer (P>0.05). Conclusion: The application of PUA with essential oils can be an effective method in dissolving ZOE based sealers. Keywords: Eucalyptol; Orange Oil; Retreatment; Solvent; Ultrasound